Hyperbaric oxygen therapy for refractory pyoderma gangrenosum: a salvage treatment. Issue 2 (18th February 2021) - de Sousa Magalhães, Rui; Moreira, Maria João; Rosa, Bruno; Cotter, José
Abstract : A 42-year-old woman with left-side ulcerative colitis (E2 – rectum to splenic flexure) was diagnosed with pyoderma gangrenosum (PG) on a persistent ulcerated wound with peripheral erythema, in the left leg's gemelar surface, associated with tenderness and pain. Due to incomplete response to wound care and oral prednisolone, treatment with infliximab was initiated. As PG remained unresponsive after 12 weeks, the patient was switched to adalimumab with concomitant oral prednisolone. Before the second induction dosage of adalimumab, the refractory PG complicated with a superinfection by Pseudomonas aeruginosa . A course of wide spectrum antibiotic therapy, daily wound care including negative pressure bandages and a physiotherapy rehabilitation programme controlled the infection, but the pyoderma persisted non-healed, with visible deep muscle layers and tendons. We proposed hyperbaric oxygen therapy in addition to weekly adalimumab, achieving full remission of the PG and recovering of the left foot's function.